ANALISIS DAMPAK RENCANA PENERAPAN ISAK 16: PENYELENGGARAAN PRASARANA KERETA API RINGAN/ LIGHT RAIL TRANSIT - Bambang Budi Prasetyo; Dian Agustia (Universitas Jember, 2018)
The purpose of this research is to analyze the impact of the implementation plan of ISAK 16 by KAI, the other purpose of this research is to discuss what issues might be faced by KAI in the plan to implement ISAK 16. This type of research is qualitative research using descriptive research method. The study found that the implementation plan of ISAK 16 by KAI will have an impact on accounting problems, the problems that will be faced are the problems of revenue recognition to construction services, the decline in the value of intangible assets and the recognition of fixed assets. Based on the impact of the implementation plan of ISAK 16 by KAI, the recognition of revenues to construction services can be fiscal corrected, the decline in the value of intangible assets can be minimized by continuing to generate future cash flows from subsequent use of assets or other assets and ask for clarification and affirmation to Dewan Standar Akuntansi Keuangan (DSAK) on the issue of recognition of property and equipment. Keywords: Infrastructure, Concession Agreement, Light Rail Transit